Evaluation of the particulate matter generated in the production of balanced products and its impact on the health of workers - Erazo Solórzano, Cyntia Yadira (2024)
The present research presents alternatives to reduce air pollution in a pig and poultry feed manufacturing plant located in Ecuador, the initial objective was to determine the type of particles present in the air, and to take preventive measures to minimize their impact on the health of workers. Field research was carried out to collect information by applying the techniques of interviews, surveys, observation sheets and through the initial risk matrix to determine the critical points of the process, with this information we proceeded to quantify the total suspended particles in the work environment. With the results obtained, control alternatives and improvements were proposed, at the source, in the environment and in the individual to achieve optimal working conditions.